2007
DOI: 10.1021/mp070049c
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Antitumor Activity of a Novel Folate-Targeted Dual Drug Conjugate

Abstract: We have designed a new type of tumor-targeted agent by tethering two different drug molecules, with distinct biological mechanisms of action, to the same ligand. This compound, named EC0225, represents the "first in class" multidrug, folate receptor (FR)-targeted agent to be disclosed. It was constructed with a single folate molecule, extended by a hydrophilic peptide-based spacer, which was in turn attached to mitomycin and Vinca alkaloid units via two separate disulfide-containing linkers. EC0225 produced po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 36 publications
1
86
0
1
Order By: Relevance
“…Preclinical (animal) imaging studies have been performed with normal and M109 tumor-bearing BALB/c mice (19,20). These studies showed scintigraphically detectable uptake in FR1 tumors placed intraperitoneally or subcutaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical (animal) imaging studies have been performed with normal and M109 tumor-bearing BALB/c mice (19,20). These studies showed scintigraphically detectable uptake in FR1 tumors placed intraperitoneally or subcutaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Various FR-targeted therapies intended to deliver potent cytotoxic antitumor agents to cells that selectively express FR are currently under development (17)(18)(19).…”
mentioning
confidence: 99%
“…The relative affinity of EC0305 was determined according to a previously published procedure (29). FR quantitation.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, "folate targeting" has been successfully applied toward the delivery of a wide variety of therapeutic-and imaging-based agents to tumors that express the FR protein (9)(10)(11)(12). Compared with their nontargeted counterparts, folic acid-bearing drugs and delivery systems have repeatedly shown greater cancer cell specificity and selectivity in numerous preclinical studies (13)(14)(15)(16)(17)(18)(19)(20). Hence, this targeting strategy leads to improvements in the safety and efficacy of anticancer agents, resulting in an increased therapeutic advantage.…”
Section: Introductionmentioning
confidence: 99%